Accounting Business Knowledge for Successful Employment - Vlasta Roška; Vesna Sesar; Ivana Martinčević (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
Accounting challenges in modern business conditions grow everyday due to that market demands and grow on a daily basis as well as the needs of management for the information's necessary to make business decisions. Accounting education is not only important for accounting profession but should be significant for all other activities such as software engineers, technical engineers or managers. Accounting does not mean just entry business events but include understanding of financial statements, tax systems and controlling. The main aim of this paper is to examine if students of other non-economic professions are aware of the importance of accounting, taxation and controlling in their education, or can they recognize their significance in future business or private life. Statistical data processing, obtained by questionnaires of University North students, was done in SPSS. The paper has proved information's that today's students start to become aware of the importance of accounting, taxation and controlling as the essential skills of the general culture to improve they business and private life. Maybe the implementation of this part of education will help young educated staff to stay in Croatia and find the part of foreign dream at home.
Keywords: M41; M49; L26; 330; accounting; business knowledge; controlling; tax; university education